2021
DOI: 10.1093/omcr/omab111
|View full text |Cite
|
Sign up to set email alerts
|

Decoding enigma: Turner syndrome with ring chromosome

Abstract: Ring chromosome X is one of the rarest with some unique phenotypical features in Turner syndrome. A young female presented to us with anasarca developed over the past 2 months due to congestive cardiac failure along with jaundice and orthopnea. She had growth retardation, intellectual disability, primary amenorrhea, lack of secondary sexual character development and dysmorphic features like low posterior hairline, shield chest and cubitus valgus. She had dilated cardiomyopathy (DCM) with intracardiac thrombus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 7 publications
1
0
0
Order By: Relevance
“…In the present study, r(X) was frequently observed, and it was often present with 45, X. The phenotypes of turner syndrome patients with r(X) have been reported to be severe, including growth retardation, intellectual disability, and multiple malformations [ 7 9 ]. The loss of X-inactive specific transcript (XIST) at Xq13 leads to functional disomy of the proximal region of chromosome X, causing the severe phenotypes [ 1 , 10 ].…”
Section: Discussionsupporting
confidence: 52%
“…In the present study, r(X) was frequently observed, and it was often present with 45, X. The phenotypes of turner syndrome patients with r(X) have been reported to be severe, including growth retardation, intellectual disability, and multiple malformations [ 7 9 ]. The loss of X-inactive specific transcript (XIST) at Xq13 leads to functional disomy of the proximal region of chromosome X, causing the severe phenotypes [ 1 , 10 ].…”
Section: Discussionsupporting
confidence: 52%